ANALISIS PERTIMBANGAN HAKIM TERHADAP KOMPETENSI RELATIF ATAS GUGATAN SEDERHANA (Studi Putusan Nomor 3/PDT.G.S/2021/PN. Rkb) - Elisa Setyowati Edison; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
An agreement is a legal relationship in the field of civil law that regulates the legal relationship between individuals in society. In the settlement of the dispute non fulfilment in court, the plaintiff can file a small claim court if the material lawsuit is at most around Rp. 500,000,000 (five hundred million rupiah) and if more than that then it can be filed a lawsuit for ordinary civil cases. Competence or authority in legal entities consists of two competencies, namely absolute competence which is an authority to the scope of the judicial environment division system, including General Justice, Religious Justice, Military Justice, and State Administrative Court. Relative Competence is the authority related to the District Court in the jurisdiction of the parties. Absolute Competence regarding a judicial body is limited by Relative Competence based on the jurisdiction of the parties to the dispute. The enforcement of the benchmark actor sequitur forum rei aims to protect the defendant and if the lawsuit is filed by other jurisdictions it is considered a legal rape against the interests of the defendant in defending himself. What is meant in the defendant's residence includes his residence, the place of certain address, or the actual place of residence which means where the defendant actually lives. The power of the judge in adjudicating and deciding cases is by independent and free power which means if a judge has been given a power over a particular case then the right to the case is the panel of judges who can decide and try the case with deliberation that is only carried out by the panel of judges in the case without any interference by outside parties.